2005
DOI: 10.1111/j.1365-2222.2005.02142.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen skin weal/radioallergosorbent test relationship in childhood populations that differ in histamine skin reactivity: a multi‐national survey

Abstract: These findings suggest that HSR--a variable that differs in schoolchildren populations from the three countries studied--independently influences the results of ASPT and its influence should be considered when ASPT are assessed in international studies. The HSR differences found in the populations reported here probably reflect a complex, dynamic, environmental interaction that should be monitored in the different parts of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Moreover, the use of antihistamines could not explain these results. In a study of 9‐year‐old children from Italy, Poland, and Libya, mean wheal diameters elicited by 10 mg/ml histamine followed a gradient with lowest diameter in Poland (3.75 mm), then Italy (4.43 mm), and highest in Libya (5.06 mm) . The mean diameter of histamine SPT in our study participants was very similar to that seen in Poland (3.68 mm).…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, the use of antihistamines could not explain these results. In a study of 9‐year‐old children from Italy, Poland, and Libya, mean wheal diameters elicited by 10 mg/ml histamine followed a gradient with lowest diameter in Poland (3.75 mm), then Italy (4.43 mm), and highest in Libya (5.06 mm) . The mean diameter of histamine SPT in our study participants was very similar to that seen in Poland (3.68 mm).…”
Section: Discussionsupporting
confidence: 74%
“…ASPTs were performed using Pepy’s method [23] in Ronciglione 1983 and1992, or the procedure suggested in the International Study of Asthma and Allergy in Children (ISAAC, Phase 2) [24] in all the other studies; in Ronciglione 1998, the same group of children underwent both procedures. The results of these studies (except those in Poprad and Ronciglione 2003) have been reported in several publications [16,17,18,19,20,21,22] (table 1, No. 1–12).…”
Section: Methodsmentioning
confidence: 76%
“…To clarify and interpret the relationship between asthma and atopy, we designed a systematic review addressing the findings from our previous surveys, single-center studies [16,17,18,19,20,21,22] and results of similar epidemiological studies available in the literature.…”
Section: Introductionmentioning
confidence: 99%